The Clash of Narratives: Armenian and Turkish Narratives on the Events of 1915 - Mustafa Tayfun ÜSTÜN (Gazi Akademik Bakış)
This paper focuses on narratives about the resettlement of Armenians in 1915. It seeks to understand how a variety of Armenian and Turkish political actors shape international politics by re-narrating the events and pursue to reconstruct the reality in a way that favours their interests. In contrast to previous works highlighting historical and legal perspectives, this paper does not aim to prove or disprove their allegations if the resettlement of Armenians was genocide or not. Rather, I propose to contribute to the literature on aesthetic sources of International Relations by analysing two movies; namely, “The Promise” and “The Ottoman Lieutenant“ to identify how the process of reconstruction and representation have been maintained by Armenian and Turkish political actors. Later on, the power and influences of narratives will be discussed in the nexus of the international relations and diaspora politics.